Less is more: calorie restriction as a therapeutic for mental health disorders - Nguyen, Jason C. D.; Govic, Antonina; Levay, Elizabeth A.; Zelko, Matthew D.; Arumugam, Thiruma V.; Penman, Jim; Johns, Terrance G.; Boskovic, Zoran (Frontiers in Psychiatry, 2025)
Anxiety, depression, and substance use disorders are prevalent mental health disorders that have debilitating health outcomes, and current treatment options are not always efficacious or tolerable. Calorie restriction (CR) has various health benefits, with research efforts focused on its effects in improving metabolic health and delaying biological aging. Recent studies have indicated that CR can also improve anxiety-, depression- and addiction-like symptoms and behavior. Similar benefits have also been observed in studies investigating a range of CR mimetics (CRMs) - molecules that mimic one or more of the physiological effects of CR without dietary restriction - indicating that both CR and CRMs could be used to assist in treating these symptoms. Here, we summarize the current evidence for the potential use of CR and select CRMs in the treatment of anxiety, depression, and addiction, as well as the possible molecular mechanisms underlying these beneficial effects. Finally, we propose novel molecular signatures that could be exploited to screen for novel CRM candidates.